Cybernotopic prochronism - Gaevskaya, Zlata (project baikal, 2026)
Architecture should be a territory of memory where the topological poetics of space is conveyed, absorbing the centuries-old metabolic experience of its structure. The formation and selection of images in folk art is based on ancient times, and is conditioned by the real economic and geographical environment in which the people live. Folk art is the soul and strength of the people. Cybernotopic prochronism implies nature-centrism and the formation of an architectural image as an architectural melody based on prescriptions of ancestors and folk traditions.